New forces of the Spanish left - from the ideology to populizm = Nowe siły hiszpańskiej lewicy - od ideologii do populizmu - Kasińska-Metryka, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Turbulence of Spanish political system are obvious, and the parliamentary elections in 2015. Will decide which party or coalition of parties will have a chance to rule. The principal questions taken considerations relate to changes within the Spanish Socialist Workers Party (PSOE). Adopted research hypothesis assumes that weaken the ideological determinants of the functioning of the party in favor of populist factors.
Keywords: parties; social democracy; political system; socjaldemokracja; system polityczny